2006
DOI: 10.1074/jbc.m511072200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Expression of Thermo-transient Receptor Potential Channels in Dental Primary Afferent Neurons

Abstract: Temperature signaling can be initiated by members of transient receptor potential family (thermo-TRP) channels. Hot and cold substances applied to teeth usually elicit pain sensation. This study investigated the expression of thermo-TRP channels in dental primary afferent neurons of the rat identified by retrograde labeling with a fluorescent dye in maxillary molars. Single cell reverse transcription-PCR and immunohistochemistry revealed expression of TRPV1, TRPM8, and TRPA1 in subsets of such neurons. Capsaic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
132
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(144 citation statements)
references
References 39 publications
(63 reference statements)
9
132
1
2
Order By: Relevance
“…Whereas localization of TRPM8 endings in the pulp is consistent with models of sensory signaling in the tooth (Matthews, 1977;Park et al, 2006), Trpm8 GFP expression in fibers entering the dentin is surprising. Strong experimental evidence suggests that sensory afferents innervating the dentin are activated via hydrodynamic receptors detecting fluid movement through dentinal tubules, a process termed the dentinal hydrodynamic theory (Matthews, 1977;Byers and Narhi, 2002;Park et al, 2006;Chidchuangchai et al, 2007).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Whereas localization of TRPM8 endings in the pulp is consistent with models of sensory signaling in the tooth (Matthews, 1977;Park et al, 2006), Trpm8 GFP expression in fibers entering the dentin is surprising. Strong experimental evidence suggests that sensory afferents innervating the dentin are activated via hydrodynamic receptors detecting fluid movement through dentinal tubules, a process termed the dentinal hydrodynamic theory (Matthews, 1977;Byers and Narhi, 2002;Park et al, 2006;Chidchuangchai et al, 2007).…”
Section: Discussionmentioning
confidence: 79%
“…Strong experimental evidence suggests that sensory afferents innervating the dentin are activated via hydrodynamic receptors detecting fluid movement through dentinal tubules, a process termed the dentinal hydrodynamic theory (Matthews, 1977;Byers and Narhi, 2002;Park et al, 2006;Chidchuangchai et al, 2007). Thus, intradental afferents are thought to be activated by a mechanism detecting changes in movement, not temperature (Chidchuangchai et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Removal of extracellular Ca 2ϩ completely blocked the acidification induced by capsaicin, showing that the influx of Ca 2ϩ is both necessary and sufficient to induce intracellular acidification by neurotransmitter receptor activation. We found that TRPV1, the receptor activated by capsaicin, was expressed only in small and intermediate sized TG neurons that are thought to be nociceptive (28). Glutamate has been shown to sensitize mechanosensitive afferents (29), and capsaicin has been shown to activate and sensitize trigeminal afferents; TRPV1 may also mediate Ca 2ϩ -dependent intracellular acidification in dorsal root ganglion neurons (7).…”
Section: Discussionmentioning
confidence: 99%
“…TRPV1, one of the transducer proteins, can generate depolarizing currents in response to noxious thermal stimuli, with an activation temperature of ϳ43°C, whereas TRPA1 is activated at ϳ17°C, a temperature that is reported as painfully cold by humans (Jordt et al, 2003;Patapoutian et al, 2003;Park et al, 2006). Although the role of TRPA1 in cold transduction is still controversial (Jordt et al, 2004;Bautista et al, 2006), TRPV1 and TRPA1 upregulation in undamaged sensory neurons has been implicated in nerve injury-induced heat and cold hypersensitivity, respectively Obata et al, 2004Obata et al, , 2005Katsura et al, 2006).…”
Section: Discussionmentioning
confidence: 99%